2021
DOI: 10.1007/s00062-021-01106-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Design and Deployment Technique on the Hydrodynamic Resistance of Flow Diverters

Abstract: Purpose Despite the high efficacy of flow diverters (FD) in treating sidewall intracranial aneurysms, failures are reported. One of the physical factors determining efficacy is the flow reducing capacity of the FD that is currently unknown to the operator. Our aim was to measure the flow reducing capacity expressed as the hydrodynamic resistance (HR), the metallic surface area (MSA) and pore density (PD) of two different FD designs and quantitatively investigate the impact of sizing and the dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Indeed, in an in vitro study, Shapiro et al 4 found that even moderate oversizing could lead to a significant increase in porosity (reduction in metal coverage), thereby lowering the blood flow diversion effect and further treatment efficiency of PED. Gyürki et al 6 found that oversizing the device by 1 mm in diameter has reduced the hydrodynamic resistance, which was a more decisive factor because it more accurately reflects the capacity of flow diversions, on average to one-fifth of its original value. Oversizing for treating an aneurysm over a nominally sized stent may produce an insufficient resistance through the aneurysm neck; therefore, the thrombosis in the sac may not be complete.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in an in vitro study, Shapiro et al 4 found that even moderate oversizing could lead to a significant increase in porosity (reduction in metal coverage), thereby lowering the blood flow diversion effect and further treatment efficiency of PED. Gyürki et al 6 found that oversizing the device by 1 mm in diameter has reduced the hydrodynamic resistance, which was a more decisive factor because it more accurately reflects the capacity of flow diversions, on average to one-fifth of its original value. Oversizing for treating an aneurysm over a nominally sized stent may produce an insufficient resistance through the aneurysm neck; therefore, the thrombosis in the sac may not be complete.…”
Section: Discussionmentioning
confidence: 99%
“…The braided structure of PED promotes high plasticity; its advantage is its high adaptability to various intracranial vessels, which also leads to the selection of a stent model for the same aneurysm that fluctuates within a specific range, thereby introducing the problem of under- or over-sizing. Several studies have reported that the size of flow diversion is strongly associated with metal coverage (amount of metal surface area covered by the device), pore density (number of pores per unit surface area), and hydrodynamic resistance, 3 6 both of which play an important role in the occlusion of aneurysms. 7 Previous research has shown that an inappropriate flow diversion model may cause accidental coverage of lateral branches, eccentric stenosis, poor wall apposition, or delayed migration, all of which could further lead to branches occlusion, endo-leak formation, disordered growth of the neointima, in-stent stenosis, or even death.…”
Section: Introductionmentioning
confidence: 99%
“…19 This TZ was reported to potentially compromise aneurysm occlusion as well. [19][20][21] Based on these reports, a strategy for optimal PED diameter and selection based on computer software was reported. 34,35 However, these conclusions on incomplete occlusion of the PED were derived from benchtop studies or computed flow simulation studies; clinical data are lacking.…”
Section: Effect Of Size Mismatch On Occlusionmentioning
confidence: 99%
“…This TZ was also reported to inhibit complete occlusion. [19][20][21] However, these reported sizing effects were based on benchtop studies, and no clinical data support the effects of these factors on clinical outcomes.…”
mentioning
confidence: 99%
“…Growing clinical experience suggested that such stents not only protect the parent vessel from coil dislocation ex aneurysm, but also influence the hemodynamic situation in the aneurysm-harboring vessel in a beneficial way. Increased metal surface coverage due to dual layer or triple layer stent constructs showed enhanced flow modifying properties [3,4], and braided stents, with even greater surface coverage than combined lasercut stents, already demonstrated a moderate flow redirecting effect [5,6]. Further developing this concept, densely braided flow diverting stents were introduced and became one of the cornerstones of modern endovascular therapy for cerebral aneurysms.…”
Section: The Concept and Basic Mechanisms Of Flow Diversionmentioning
confidence: 99%